Social Rehabilitation and Surgery in Leprosy - Palande, Dinkar D. (2002)
The image of leprosy in the community causes a reduction in the socioeconomic status of the affected and the family. The prevalence of disability is on the increase and because of neglect, the severity of established disability is also increasing. In fact, untreated disability worsens and leads to dehabilitation and send negative messages to the community. We know how to negate, lessen or control disability but full application of this knowledge has not yet become a part of leprosy control programs or, if present, still it has a low priority fact, untreated disability worsens andleads to dehabilitation and send negative messages to the community. On the other hand a rehabilitated person is a force for positive behaviour. Early disability correction prevents dehabilitation. Correction of disability sends positive messages and together with transfer of information,education and counseling restore socioeconomic status. Surgery is aimed at optimum correction of deformity and disability and consists of reconstructive surgery, cosmetic surgery, ulcer surgery and salvage surgery. Very little evidence-based information is available on the impact ofsurgery in the rehabilitation of leprosy affected persons. LEPRA had sponsored one study on impact of surgery in Sonepur district of Orissa by National Institute of Social Sciences in 1998 wherein 140 individuals who had 226 operations between 1994 and 1997 were studied, in the majority of persons the income before disease, which was very much reduced during the disease and hospitalization, was regained after surgery. In others it was in the process of being regained. The acceptance by the community also increased after surgery. Before the disease non-acceptanceby the family was more than by the community.